If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x = 2(0) + 3 Multiply 2 * 0 x = 0 + 3 Anything times zero is zero. x = 0 + 3 Combine like terms: 0 + 3 = 3 x = 3 Solving x = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Simplifying x = 3
| -x-3x-77=39 | | x+5-15=10 | | 2x+(-39)=-16 | | 7=1-2n | | 9e^2x+1=7e^5x^2 | | 4a-(-16)=32 | | -(6u-w)-4(-5w-6u)= | | a=2d/10^2 | | 3+4ln(x)=7 | | 6(x-2)=2(2x+3) | | -3t^2+36t=60 | | 5(x-2)2+6=86 | | 8y+4-2y=y+1 | | 6y-30y=-46 | | 6y-30y= | | 4x^2-24x-224=0 | | 9c=14c-15 | | (2r+5)(r+2)=0 | | 2/3x-1/2y=14 | | 7/(w^2.5)=0.5 | | -6n-20=2n+4(3n) | | 7/w^2.5=0.5 | | 12b-30=20b-70 | | -112-9x-11x=148 | | 4y-83=2y-37 | | a=0.9*800 | | -5(-6y+10)-5y-3= | | 3z-73=z+1 | | 4x^2+24x-224=0 | | 4x^2+12x-224=0 | | x+30=2x+29 | | 2x^2+24x-224=0 |